A new genus of isophlebioid damsel-dragonflies (Odonata: Isophlebioptera: Campterophlebiidae) from the Middle Jurassic of China - Nel, A.; Huang, D.-Y.; Lin, Q.-B. (Zootaxa, 2007)
Sinokaratawia prokopi gen. nov., sp. nov. is the fifth representative of the Campterophlebiidae from the Chinese Middle Jurassic Jiulongshan Formation, which corresponds to one of the most diverse fauna of isophlebioid damsel-dragonflies. The synapomorphies for the Campterophlebiidae and Isophlebiidae are discussed.